Mulheres no espaço urbano de Sorocaba-SP: movimentos de mulheres e a construção de suas territorialidades - Nunes, Renata (2019)
This dissertation aims to understand the making of spaces from women strife, militancy and life in the city of Sorocaba-SP, through the actions of different kinds of women movement.As study cases, the actions linked to the Women Rights City Council elected for the 2018/2020 biennium were analyzed as a way to understand the institutionalized space production in contrast to everyday actions of the leading women. Based on these women's life histories, we sought to analyze the dialectical relationship between the Spaces of Representation and the Representational Spaces (according to the conception of Henri Lefebvre) to understand the formation of territorialities that arise from the demands of daily life itself.